1992
DOI: 10.1111/j.1365-2362.1992.tb01819.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of insulin clearance and secretion to insulin sensitivity in non‐diabetic Mexican Americans

Abstract: The antecedents of type II diabetes, while still controversial, are thought to involve decreased insulin sensitivity and compensatory hypersecretion of insulin. Mexican Americans have a three-fold excess risk of type II diabetes and non-diabetic Mexican Americans are characterized by hyperinsulinaemia and insulin resistance. Few data exist, however, on whether there are defects in insulin secretion and/or clearance in this population. We examined insulin sensitivity, secretion and clearance using combined insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 42 publications
7
31
1
Order By: Relevance
“…Differences in insulin sensitivity and ␤-cell function between non-Hispanic whites and various Latino subgroups remain to be determined. Our findings suggest that data obtained from previous studies may not be applicable to other Latinos as a group, particularly the findings that Latinos of Mexican (San Antonio, TX) and Spanish (San Luis Valley, CO) origin are less insulin sensitive than non-Hispanic whites (31,32). These findings may have been inappropriately extrapolated to other non-MexicanAmerican Latino subgroups, as studies in other Latino subgroups are limited.…”
Section: ␤-Cell Functioncontrasting
confidence: 37%
“…Differences in insulin sensitivity and ␤-cell function between non-Hispanic whites and various Latino subgroups remain to be determined. Our findings suggest that data obtained from previous studies may not be applicable to other Latinos as a group, particularly the findings that Latinos of Mexican (San Antonio, TX) and Spanish (San Luis Valley, CO) origin are less insulin sensitive than non-Hispanic whites (31,32). These findings may have been inappropriately extrapolated to other non-MexicanAmerican Latino subgroups, as studies in other Latino subgroups are limited.…”
Section: ␤-Cell Functioncontrasting
confidence: 37%
“…Our observations lead us to propose a second complimentary mechanism whereby peripheral insulin levels are maintained through a decrease in hepatic insulin clearance. The C-peptide:insulin ratio is an index of hepatic insulin clearance [31][32][33], and was found to be markedly decreased in the relatives (Table 2). Haffner and colleagues reported decreased hepatic insulin clearance in non-diabetic Mexican Americans when compared with non-Hispanic white control subjects [33], and proposed that it represented an adaptive response to maintain adequate circulating insulin levels in the presence of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] It has been suggested that decreased insulin clearance compensates for decreased insulin sensitivity or vice versa. [23][24][25][26][27][28] However, experimental models suggest that the mechanisms of insulin clearance and action may be physiologically linked. In hepatocytes, the binding of insulin to its receptor is the first step for initiation of intracellular insulin signaling cascade and for endocytosis and degradation of insulin by insulin-degrading enzyme.…”
Section: Discussionmentioning
confidence: 99%